Strategi Harga, Kualitas Pelayanan, dan Kualitas Produk Terhadap Kepuasan Konsumen Indah Bordir Sidoarjo - Rifai, M Fariz; Supardi, Supardi; Febriansah, Rizky Eka (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this research is to determine the role of Price Strategy, Service Quality and Product Quality on Consumer Satisfaction at Indah Bordir Sidoarjo. This research methodology uses a quantitative type of research. This research sample was taken using a non-probability sampling technique with accidental sampling type. Respondents in this study had criteria, namely people who had purchased Indah Embroidery products. The sample in this study was 96 people who were calculated using the Chocran formula. The data analysis technique uses the help of the smart-PLS version 3.0 application. The findings of this research show that Price Strategy has a positive and significant effect on Consumer Satisfaction at Indah Bordir Sidoarjo, Service Quality has a positive and significant effect on Consumer Satisfaction at Indah Bordir Sidoarjo and Product Quality has a positive and significant effect on Consumer Satisfaction at Indah Bordir Sidoarjo. Suggestions for further research are expected to use a larger population by adding other independent variables to further expand information regarding the factors causing consumer satisfaction.